Association between earthquake and equatorial waves in outgoing longwave radiation over South East Asia - Lal, M.; Bhagavathiammal, G.J. (My University, 2016)
In the present study, efforts have been made to correlate the equatorial waves in outgoing longwave radiation (OLR) and seismic activities in South East Asian region. The OLR data has been obtained from NOAA Climate Prediction Centre web site. The earthquake information has been obtained from United States Geological Survey (USGS) Earthquake Information Centre. This paper presents observations for few earthquakes, including the ones on 26 January 2001 at Bhuj, India and on 26 December 2004 at Sumatra, Indonesia. The normal days OLR has been compared to the OLR recorded during the seismic events. It has been observed that there is significant enhancement in OLR few days before the earthquake event. The Morlet 6.6 wavelet analysis shows the presence of equatorial waves in equatorial OLR for a period of about 6-16 days during and about 80 days before the earthquake. The OLR data is analysed in such a way that the other possible effects are minimized. The anomalous increase and presence of planetary waves before 80 days of seismic event shows great potential in providing early warning of a disastrous earthquake. It may be noted that these waves are generated only in the equatorial region irrespective of strong/severe earthquake location.
Keywords: Earthquake; Equatorial wave; Planetary wave; Outgoing longwave radiation (OLR); Seismic event